Renal Parenchyma to Hydronephrosis Area Ratio (PHAR) as a Predictor of Future Surgical Intervention for Infants With High-grade Prenatal Hydronephrosis. - Rickard, Mandy; Lorenzo, Armando J.; Braga, Luis H. (Urology, 2017)
Objective: To explore the potential value of an objective assessment, renal parenchyma to hydronephrosis area ratio (PHAR), as an early predictor of surgery.Methods: Initial sagittal renal ultrasound (US) images of patients prospectively entered into a prenatal hydronephrosis database from January 2008 to January 2016 with baseline Society for Fetal Urology (SFU) grades III and IV prenatal hydronephrosis, without vesicoureteral reflux, were evaluated using the National Institutes of Health-sponsored image processing software. PHAR, anteroposterior diameter, SFU grade, and urinary tract dilation risk categories were contrasted with nuclear scan data (differential renal function and drainage time [t1/2]) and analyzed for predictive value in determining the decision to proceed with surgery by drawing receiver operating characteristic curves.Results: Out of 196 infants (162 male; 138 left sided hydronephrosis), 58 (30%) underwent surgery to address obstruction. Surgical patients compared with those managed conservatively had longer t1/2 (60 vs 18 min; P < .01) and lower differential renal function (46 vs 50%; P = .01). Of the initial US parameters, PHAR (area under the curve = 0.816; P < .001) had a better predictive performance than anteroposterior diameter, SFU grade, or urinary tract dilation classification. PHAR values correlated with subsequent parameters obtained on nuclear scan.Conclusion: PHAR is a promising parameter that can be estimated on presentation US to help predict future need for surgery in newborns with high-grade hydronephrosis.